PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAAN BASIC MATERIAL DI BEI - Yadi, Amri; Busra, Busra (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
The study aims to test the impact of the capital structure and firm size of the company on profitability. The capital structure is measured by the debt-to-equity ratio (DER), the firm size of the corporation is measured by the natural logarithm (Ln), and profitability is measured by the return on assets . (ROA). This research is quantitative. The population used is the entire Basic Materials sector company listed on the Indonesian Stock Exchange (BEI) for the observation period 2018–2022. Data collection techniques use purposive sampling. Nine mining companies met the criteria. Total data of 45 data points, with secondary data of the annual report taken from www.idx.co.id and the annual report of the company. The data analysis technique uses double linear regression with Eviews 12. The results of the research concluded that the capital structure partially affects profitability positively, and the size of the company does not affect profitability. Meanwhile, simultaneously, the capital structure and size of the company influence profitability.